Self-excitation recycled aggregate concrete and preparation method thereof

By using self-exciting materials and nano-scale SAP particles for modification in regenerated aggregate concrete, the problems of poor strength enhancement and high cost in the early stage are solved, and efficient mechanical performance improvement and self-healing effect are achieved, suitable for large-scale application.

CN119176706APending Publication Date: 2024-12-24INST OF ECONOMIC & TECH STATE GRID HEBEI ELECTRIC POWER +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411143219.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-20
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

In the prior art, the early strength enhancement effect of recycled aggregate concrete is poor, nano silica is expensive and difficult to apply on a large scale, CO2 maintenance methods are limited in application in actual projects, and may lead to the risk of steel bar corrosion.

Method used

Self-exciting materials and nano-sized SAP particles are used to modify the regenerated coarse aggregate, reduce porosity, enhance the bonding performance, and combine nano-sized SAP particles with regenerated coarse aggregate, and add modifiers and microcrystalline cellulose to form Self-healing hydrogels that fill pores and promote bonding.

Benefits of technology

It significantly improves the mechanical properties of regenerated aggregate concrete, reduces porosity and crack generation, achieves self-healing effect, improves compressive strength, and reduces production costs.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of cement-based building materials, in particular to self-excitation recycled aggregate concrete and a preparation method thereof.A self-excitation material is adopted as a cementing material, recycled coarse aggregate is modified through nanoscale SAP particles, the porosity of the recycled coarse aggregate is reduced, and the bonding performance of the recycled coarse aggregate and the cementing material is enhanced; therefore, the mechanical property of the self-excitation recycled aggregate concrete is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cement-based building materials, in particular to a self-stimulated recycled aggregate concrete and a preparation method thereof. Background Art

[0002] Recycled aggregate refers to the aggregate obtained by crushing and screening the waste concrete after the demolition of buildings. Since the surface of recycled aggregate is covered with a layer of hardened cement paste with many holes and cracks, it has high porosity, poor bonding performance and low compressive strength, which makes its performance often inferior to that of natural aggregate, restricting the application of recycled aggregate in the construction industry. Therefore, how to achieve the recycling of recycled aggregate has always been a hot topic in the construction field at home and abroad.

[0003] At present, the methods for strengthening the performance of recycled aggregates mainly focus on the following two aspects: (1) using grinding, acid immersion and microwave heating methods to remove the hardened cement paste covering the surface of recycled aggregates; (2) using water glass immersion, polyvinyl alcohol immersion and other methods to strengthen the hardened cement paste covering the surface of recycled aggregates. Although these methods can make up for the defects of recycled aggregates, they are limited in economy and applicability, and may also cause new environmental pollution.

[0004] Reference 1 (Liu Junhui, Liu Bingyue, Ou Sihua, et al. Research on the influence of nano-silica on the performance of recycled aggregate concrete [J]. Materials Research and Application, 2022, 16 (02): 228-233.) published a method for improving the performance of recycled aggregate concrete. The method is to improve the performance of concrete by adding nano-silica, taking advantage of its small particle size, large specific surface area and high volcanic ash activity. At the same time, nano-silica can also fill the pore structure of concrete to make it denser. Reference 2 (Liang CF, Wang SC, Cai ZD, et al. Effects of CO2 curing methods on frostresistance and mechanical properties of recycled aggregate concrete [J]. Case Studies in Construction Materials, 2024, e02973.) published a method for improving the mechanical properties of recycled aggregate concrete by changing the curing method. The method is to introduce CO2 into the recycled aggregate concrete for curing, and utilize CO2 to promote the carbonization of the recycled aggregate concrete, generate carbonization products and fill the matrix pores, thereby improving the mechanical properties of the recycled aggregate concrete.

[0005] The shortcomings of the above technologies are: (1) Document 1 describes the improvement of the performance of recycled aggregate concrete by adding nano-silicon dioxide. Although this preparation method is helpful for the recycling of recycled aggregate, the preparation process only involves mixing nano-silicon dioxide with part of the mixing water and then adding it to the concrete. No modification is performed on the recycled aggregate, resulting in poor early strength improvement of the recycled aggregate concrete. At the same time, excessive silicon dioxide can also cause dehydration of the matrix and crack formation. In addition, the price of nano-silicon dioxide is relatively high, which is not conducive to the large-scale application of recycled aggregate concrete. (2) Document 2 describes the use of CO2 to cure recycled aggregate concrete to improve its performance. In the early stages of curing, the carbonation rate of recycled aggregate concrete is relatively fast, and more calcium carbonate can be generated. As the curing time increases, the generated calcium carbonate gradually blocks the pores and inhibits the penetration of CO2, resulting in the lack of obvious improvement in concrete strength in the later stages. Although increasing CO2 pressure and curing time can improve the performance of recycled aggregate concrete, it is currently limited to the laboratory stage and is difficult to apply in actual projects. In addition, too long a curing time can also cause some hydration products to dissolve, weakening the strength of recycled aggregate concrete. CO2 curing will also reduce the pH value of the concrete surface, and subsequent cement hydration will make it difficult to restore the pH value to its original level, which increases the risk of steel corrosion and limits the application scope of recycled aggregate concrete. Summary of the invention

[0006] In order to solve the problems existing in the prior art, the present invention provides a self-excited recycled aggregate concrete and a preparation method thereof, adopts a self-excited material as a cementitious material, and uses nano-scale SAP particles to modify the recycled coarse aggregate, thereby reducing the porosity of the recycled coarse aggregate and enhancing the bonding performance between the recycled coarse aggregate and the cementitious material, so as to improve the mechanical properties of the self-excited recycled aggregate concrete.

[0007] Specifically, the self-excited recycled aggregate concrete of the present invention is composed of the following raw materials in parts by weight:

[0008] 90-110 parts of steel slag powder, 190-210 parts of mineral powder, 190-210 parts of gypsum, 50-60 parts of alkali activator, 580-620 parts of fine aggregate, 980-1000 parts of modified recycled coarse aggregate, 10-12 parts of water reducer, and 200-210 parts of water.

[0009] Wherein, the modified recycled coarse aggregate preparation process is:

[0010] a. Grind and sieve the SAP particles to obtain nano-sized SAP particles.

[0011] b. Heat and stir ethyl orthosilicate and waterborne polyurethane to obtain a modifier.

[0012] c. Mix the nano-sized SAP particles and the recycled coarse aggregate evenly, heat them, add a modifier, then add microcrystalline cellulose, stir evenly, and cool to obtain a product wherein the mass ratio of the nano-sized SAP particles, tetraethyl orthosilicate, water-based polyurethane, recycled coarse aggregate, and microcrystalline cellulose is (1.5-2.5):(20-22):(20-22):100:(4-5).

[0013] Recycled coarse aggregate has high porosity, poor bonding performance and low compressive strength. The key factor to improve the mechanical properties of concrete prepared with recycled coarse aggregate is how to improve the pore structure of recycled coarse aggregate and strengthen the performance of recycled coarse aggregate. The inventor cooperated with universities to carry out industry-university-research technology transformation. By introducing nano-scale SAP particles and combining them with recycled coarse aggregate, the nano-scale SAP adheres to the surface and cracks of the recycled coarse aggregate. In the process, a modifier composed of ethyl orthosilicate and water-based polyurethane is added to further enhance the bonding between the nano-scale SAP particles and the recycled coarse aggregate.

[0014] The nano-sized SAP particles of the present invention form hydrogel-like substances after absorbing water, which not only fill the pores of the recycled coarse aggregate, but also exert self-repairing properties, realize self-healing of the cracks of the recycled coarse aggregate and the self-excited concrete cracks, and reduce the generation and extension of the cracks. The heating process can remove excess water and promote the modification effect of the recycled coarse aggregate. The addition of microcrystalline cellulose can promote the improvement of the fluidity of the modifier, make the nano-sized SAP particles adhere more evenly, and avoid the agglomeration of the modifier.

[0015] Preferably, the particle size of the steel slag powder is 80-150 μm.

[0016] Preferably, the particle size of the mineral powder is 20-100 μm.

[0017] Preferably, the gypsum is at least one of phosphogypsum and desulfurized gypsum.

[0018] Preferably, the alkali activator is at least one of water glass and slaked lime.

[0019] Preferably, the fine aggregate is at least one of quartz sand and river sand.

[0020] Preferably, the water reducer is a polycarboxylate water reducer.

[0021] Preferably, the SAP particles in step a are sodium polyacrylate-polyacrylamide type SAP, and the particle size is 0.1-20 mm.

[0022] Preferably, the sieving in step a uses a negative pressure sieving instrument.

[0023] Preferably, the particle size of the nano-scale SAP particles in step a is 50-100 nm.

[0024] Preferably, the temperature in step b is heated to 40°C.

[0025] Preferably, the particle size of the recycled coarse aggregate in step c is 5-16 mm.

[0026] Preferably, the temperature is heated to 80° C. in step c.

[0027] Preferably, the microcrystalline cellulose in step c is cellulose with a polymerization degree reaching the limit obtained by hydrolyzing natural plant cellulose, and is a white crystalline powder with a particle size of 20-60 nm.

[0028] The present invention also relates to a method for preparing the self-excited recycled aggregate concrete, which specifically comprises the following steps:

[0029] 1) Weigh each raw material by weight,

[0030] 2) Add steel slag powder, mineral powder, gypsum and fine aggregate into the mixer and mix well.

[0031] 3) Add modified recycled coarse aggregate to the mixer and mix evenly.

[0032] 4) Add water reducer to water and mix well to obtain admixture solution.

[0033] 5) Add the additive solution and alkali activator into the mixer and mix well to obtain slurry.

[0034] 6) The slurry is molded, demoulded and cured.

[0035] Preferably, step 6) curing adopts standard curing.

[0036] The present invention has the following technical advantages:

[0037] 1. The present invention uses self-excited materials as cementitious materials and adds recycled coarse aggregate to recycle bulk solid waste, reduce costs and increase efficiency.

[0038] 2. The present invention introduces nano-scale SAP particles to bond and fill the recycled coarse aggregate, thereby reducing the porosity of the recycled coarse aggregate.

[0039] 3. The present invention adopts modifier and microcrystalline cellulose to improve the combination effect of nano-scale SAP particles and recycled coarse aggregate, and comprehensively improves the mechanical properties of self-excited recycled aggregate concrete. DETAILED DESCRIPTION

[0040] In order to characterize the technical effect of the present invention, self-excited recycled aggregate concrete was prepared and its mechanical properties were tested. Among them, the particle size of steel slag powder is 80-150μm, the particle size of mineral powder is 20-100μm, the fine aggregate is river sand, the water reducer is polycarboxylate water reducer, the particle size of nano-SAP particles is 50-100nm, the particle size of recycled coarse aggregate is 5-16mm, and the particle size of microcrystalline cellulose is 20-60nm.

[0041] Example 1

[0042] Self-stimulated recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0043] 100 parts of steel slag powder, 210 parts of mineral powder, 190 parts of desulfurized gypsum, 60 parts of water glass, 590 parts of fine aggregate, 1000 parts of modified recycled coarse aggregate, 11 parts of water reducer, and 210 parts of water.

[0044] Wherein, the modified recycled coarse aggregate preparation process is:

[0045] a. Grind and sieve the SAP particles to obtain nano-sized SAP particles.

[0046] b. Heat ethyl orthosilicate and waterborne polyurethane to 40°C and stir evenly to obtain a modifier.

[0047] c. Mix the nano-sized SAP particles and the recycled coarse aggregate evenly, heat to 80° C., add a modifier, then add microcrystalline cellulose, stir evenly, and cool to obtain the product, wherein the mass ratio of the nano-sized SAP particles, tetraethyl orthosilicate, water-based polyurethane, recycled coarse aggregate, and microcrystalline cellulose is 1.5:21:21:100:4.6.

[0048] After testing, the 3d compressive strength of concrete is 23.6MPa, the 7d compressive strength is 34.9MPa, and the 28d compressive strength is 46.0MPa.

[0049] Example 2

[0050] Self-stimulated recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0051] 90 parts of steel slag powder, 200 parts of mineral powder, 200 parts of phosphogypsum, 50 parts of slaked lime, 580 parts of fine aggregate, 1000 parts of modified recycled coarse aggregate, 12 parts of water reducer, and 200 parts of water.

[0052] Wherein, the modified recycled coarse aggregate preparation process is:

[0053] a. Grind and sieve the SAP particles to obtain nano-sized SAP particles.

[0054] b. Heat ethyl orthosilicate and waterborne polyurethane to 40°C and stir evenly to obtain a modifier.

[0055] c. Mix the nano-sized SAP particles and the recycled coarse aggregate evenly, heat to 80° C., add a modifier, then add microcrystalline cellulose, stir evenly, and cool to obtain the product, wherein the mass ratio of the nano-sized SAP particles, tetraethyl orthosilicate, water-based polyurethane, recycled coarse aggregate, and microcrystalline cellulose is 2.5:22:20:100:5.

[0056] After testing, the concrete's 3d compressive strength is 25.3MPa, 7d compressive strength is 36.7MPa, and 28d compressive strength is 48.7MPa.

[0057] Example 3

[0058] Self-stimulated recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0059] 110 parts of steel slag powder, 190 parts of mineral powder, 210 parts of desulfurized gypsum, 55 parts of water glass, 620 parts of fine aggregate, 980 parts of modified recycled coarse aggregate, 10 parts of water reducer, and 200 parts of water.

[0060] Wherein, the modified recycled coarse aggregate preparation process is:

[0061] a. Grind and sieve the SAP particles to obtain nano-sized SAP particles.

[0062] b. Heat ethyl orthosilicate and waterborne polyurethane to 40°C and stir evenly to obtain a modifier.

[0063] c. Mix the nano-sized SAP particles and the recycled coarse aggregate evenly, heat to 80° C., add a modifier, then add microcrystalline cellulose, stir evenly, and cool to obtain a product wherein the mass ratio of the nano-sized SAP particles, tetraethyl orthosilicate, water-based polyurethane, recycled coarse aggregate, and microcrystalline cellulose is 2:20:22:100:4.

[0064] After testing, the concrete's 3d compressive strength is 27.2MPa, 7d compressive strength is 36.0MPa, and 28d compressive strength is 49.1MPa.

[0065] Comparative Example 1

[0066] Self-stimulated recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0067] 100 parts of steel slag powder, 210 parts of mineral powder, 190 parts of desulfurized gypsum, 60 parts of water glass, 590 parts of fine aggregate, 1000 parts of recycled coarse aggregate, 11 parts of water reducer, and 210 parts of water.

[0068] After testing, the 3d compressive strength of concrete is 13.5MPa, the 7d compressive strength is 20.9MPa, and the 28d compressive strength is 31.6MPa.

[0069] Comparative Example 2

[0070] Self-stimulated recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0071] 100 parts of steel slag powder, 210 parts of mineral powder, 190 parts of desulfurized gypsum, 60 parts of water glass, 590 parts of fine aggregate, 1000 parts of modified recycled coarse aggregate, 11 parts of water reducer, and 210 parts of water.

[0072] Wherein, the modified recycled coarse aggregate preparation process is:

[0073] a. Grind and sieve the SAP particles to obtain nano-sized SAP particles.

[0074] b. Heat the waterborne polyurethane to 40°C and stir evenly to obtain the modifier.

[0075] c. Mix the nano-sized SAP particles and the recycled coarse aggregate evenly, heat to 80° C., add a modifier, then add microcrystalline cellulose, stir evenly, and cool to obtain the product, wherein the mass ratio of the nano-sized SAP particles, water-based polyurethane, recycled coarse aggregate, and microcrystalline cellulose is 1.5:21:100:4.6.

[0076] After testing, the 3d compressive strength of concrete is 14.5MPa, the 7d compressive strength is 21.3MPa, and the 28d compressive strength is 32.6MPa.

[0077] Comparative Example 3

[0078] Self-stimulated recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0079] 100 parts of steel slag powder, 210 parts of mineral powder, 190 parts of desulfurized gypsum, 60 parts of water glass, 590 parts of fine aggregate, 1000 parts of modified recycled coarse aggregate, 11 parts of water reducer, and 210 parts of water.

[0080] Wherein, the modified recycled coarse aggregate preparation process is:

[0081] a. Grind and sieve the SAP particles to obtain 100-200 μm micron-sized SAP particles.

[0082] b. Heat ethyl orthosilicate and waterborne polyurethane to 40°C and stir evenly to obtain a modifier.

[0083] c. Mix the micron-sized SAP particles and the recycled coarse aggregate evenly, heat to 80° C., add a modifier, then add microcrystalline cellulose, stir evenly, and cool to obtain a product wherein the mass ratio of the micron-sized SAP particles, tetraethyl orthosilicate, water-based polyurethane, recycled coarse aggregate, and microcrystalline cellulose is 1.5:21:21:100:4.6.

[0084] After testing, the concrete's 3d compressive strength is 18.2MPa, 7d compressive strength is 25.6MPa, and 28d compressive strength is 38.3MPa.

[0085] Comparative Example 4

[0086] Self-stimulated recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0087] 100 parts of steel slag powder, 210 parts of mineral powder, 190 parts of desulfurized gypsum, 60 parts of water glass, 590 parts of fine aggregate, 1000 parts of modified recycled coarse aggregate, 11 parts of water reducer, and 210 parts of water.

[0088] Wherein, the modified recycled coarse aggregate preparation process is:

[0089] a. Grind and sieve the SAP particles to obtain nano-sized SAP particles.

[0090] b. Heat ethyl orthosilicate and waterborne polyurethane to 40°C and stir evenly to obtain a modifier.

[0091] c. Mix the nano-sized SAP particles and the recycled coarse aggregate evenly, heat to 80° C., add a modifier, stir evenly, and cool to obtain a product wherein the mass ratio of the nano-sized SAP particles, tetraethyl orthosilicate, waterborne polyurethane, and recycled coarse aggregate is 1.5:21:21:100.

[0092] After testing, the 3d compressive strength of concrete is 12.2MPa, the 7d compressive strength is 26.4MPa, and the 28d compressive strength is 33.7MPa.

[0093] Comparative Example 5

[0094] Self-stimulated recycled aggregate concrete is composed of the following raw materials in parts by weight:

[0095] 100 parts of steel slag powder, 210 parts of mineral powder, 190 parts of desulfurized gypsum, 60 parts of water glass, 590 parts of fine aggregate, 1000 parts of recycled coarse aggregate, 15 parts of nano-scale SAP particles, 11 parts of water reducer, and 210 parts of water.

[0096] The nano-scale SAP particle preparation process comprises grinding and sieving SAP particles to obtain nano-scale SAP particles.

[0097] After testing, the 3d compressive strength of concrete is 18.7MPa, the 7d compressive strength is 26.9MPa, and the 28d compressive strength is 38.1MPa.

[0098] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A self-stimulated recycled aggregate concrete, characterized in that: It is composed of the following raw materials in parts by weight: 90-110 parts of steel slag powder, 190-210 parts of mineral powder, 190-210 parts of gypsum, 50-60 parts of alkali activator, 580-620 parts of fine aggregate, 980-1000 parts of modified recycled coarse aggregate, 10-12 parts of water reducer, 200-210 parts of water, The modified recycled coarse aggregate preparation process is: a. Grind and sieve the SAP particles to obtain nano-sized SAP particles. b. Heat and stir ethyl orthosilicate and waterborne polyurethane to obtain a modifier. c. Mix the nano-sized SAP particles and the recycled coarse aggregate evenly, heat them, add a modifier, then add microcrystalline cellulose, stir evenly, and cool to obtain a product wherein the mass ratio of the nano-sized SAP particles, tetraethyl orthosilicate, water-based polyurethane, recycled coarse aggregate, and microcrystalline cellulose is (1.5-2.5):(20-22):(20-22):100:(4-5).

2. The self-stimulated recycled aggregate concrete according to claim 1, characterized in that: The particle size of the steel slag powder is 80-150 μm.

3. The self-stimulated recycled aggregate concrete according to claim 1, characterized in that: The particle size of the mineral powder is 20-100 μm.

4. The self-stimulated recycled aggregate concrete according to claim 1, characterized in that: The gypsum is at least one of phosphogypsum and desulfurized gypsum.

5. The self-stimulated recycled aggregate concrete according to claim 1, characterized in that: The alkali activator is at least one of water glass and slaked lime.

6. The self-stimulated recycled aggregate concrete according to claim 1, characterized in that: The fine aggregate is at least one of quartz sand and river sand.

7. The self-stimulated recycled aggregate concrete according to claim 1, characterized in that: The water reducer is a polycarboxylate water reducer.

8. The self-stimulated recycled aggregate concrete according to claim 1, characterized in that: In step a, the particle size of the nano-scale SAP particles is 50-100 nm.

9. The self-stimulated recycled aggregate concrete according to claim 1, characterized in that: In step c, the particle size of the recycled coarse aggregate is 5-16 mm.

10. The method for preparing the self-excited recycled aggregate concrete according to any one of claims 1 to 9, characterized in that: The steps include: 1) Weigh each raw material by weight, 2) Add steel slag powder, mineral powder, gypsum and fine aggregate into the mixer and mix well. 3) Add modified recycled coarse aggregate to the mixer and mix evenly. 4) Add water reducer to water and mix well to obtain admixture solution. 5) Add the additive solution and alkali activator into the mixer and mix well to obtain slurry. 6) The slurry is molded, demoulded and cured.

Citation Information

Cited By

  • Recycled aggregate concrete 3D printing wall material modification process

    CN120483568A

  • A modification process for 3D printed wall materials using recycled aggregate concrete

    CN120483568B